Should I book another hotel? The effects of sickness and ethnicity on customer brand loyalty and positive word of mouth - Correia Leal, C.; Ferreira, A. I. (International Journal of Hospitality Management, 2020)
Sickness presenteeism is working despite feeling sick. Although presenteeism prevails across different job sectors, few studies have focused on how it affects the hospitality sector. This study applied a quasi-experimental method to investigate how sick employees’ presence affects customers’ fear of contagion and, consequently, customer brand loyalty (i.e., return intentions) and positive word of mouth (i.e., recommendation intentions) due to perceived service failure. The effects of ethnicity on customers’ intentions were also explored. Data were collected from 581 participants. The results reveal that, when hospitality employees appear to be sick, customers have weaker recommendation and return intentions compared to when employees do not show any sickness. In addition, our results show that due to perceived ethnic dissimilarity, customers do not tend to withdraw from non-similar sick employees, not showing weaker recommendation and rebooking intentions toward tourist accommodations. This research enriches the very well stablished literature on consumer-brand relationships, sickness presenteeism and social cognition, as well as furthering practice by showing that sickness presenteeism, when correctly managed, can generate organizational advantages.